Locomotory control in amphioxus larvae: new insights from neurotransmitter data. Issue 1 (December 2017) - Lacalli, Thurston; Candiani, Simona
Abstract Amphioxus larvae have a midbrain-level locomotory control center whose overall organization is known from serial TEM reconstructions. How it functions has been a puzzle, owing to uncertainty as to the transmitters used by each class of neurons, but this has recently become clearer. We summarize what is now known, and correct past misconceptions: The large paired neurons at the core of the control center are glutamatergic, and hence excitatory, the commissural neurons are GABAergic, hence probably inhibitory, and both motoneurons and ipsilateral projection neurons are cholinergic, suggesting that the latter, a class of interneurons, may be derived evolutionarily from the former. The data clarify some aspects of how fast and slow swimming are controlled and prevented from interfering with one another, but leave open the source of pacemaker activity, which could reside in the large paired neurons or circuits associated with them. A unusual type of non-synaptic junction links the fast and slow systems, but how these junctions function is open to interpretation, depending chiefly on whether they act to couple adjacent cells independent of cell type, or can have differential effects that vary with cell type. Some evolutionary implications are discussed.